2017
DOI: 10.1093/mnras/stx992
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Type Ic SN 2004aw: a moderately energetic explosion of a massive C+O star without a GRB

Abstract: An analysis of the Type Ic supernova (SN) 2004aw is performed by means of models of the photospheric and nebular spectra and of the bolometric light curve. SN 2004aw is shown not to be "broad-lined", contrary to previous claims, but rather a "fast-lined" SN Ic. The spectral resemblance to the narrow-lined Type Ic SN 1994I, combined with the strong nebular [O i] emission and the broad light curve, point to a moderately energetic explosion of a massive C+O star. The ejected 56 Ni mass is ≈ 0.20 M ⊙ . The ejecta … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 76 publications
6
66
0
Order By: Relevance
“…The partially mixed model has better success. This is also backed by the fitted abundance structure in Mazzali et al (2017), which shows fairly strong 56 Ni and Fe group mixing outside the inner regions. This type of mixing is seen in Figure 4.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The partially mixed model has better success. This is also backed by the fitted abundance structure in Mazzali et al (2017), which shows fairly strong 56 Ni and Fe group mixing outside the inner regions. This type of mixing is seen in Figure 4.…”
Section: Discussionmentioning
confidence: 53%
“…The models in this work do follow Arnett's models to an extent but we do not expect a replication of the exact results. Arnett assumes a point-like distribution of 56 Ni, which is not realistic (see, e.g., Mazzali et al 2017) and is not what we use. As 56 Ni is produced further out with increasing E k , diffusion of photons is easier and peak is reached earlier.…”
Section: Light Curvesmentioning
confidence: 99%
“…From our fitting, the value of τ m =11.6 days. Based on our measurement of velocities from the FeII lines (assumed to be nearly photospheric) in the observed spectra, we have set v ph =9700 km s 51 erg (see also Mazzali et al 2017). We note that Taddia et al (2015), from their sample of SNe Ic, estimated mean values of M( 56 Ni)=0.33 M e , E K = 1.75×10 51 erg, and large M ej =5.75 M e .…”
Section: Quasi-bolometric Light Curvementioning
confidence: 99%
“…The affect of vary ejecta mass was also explored. Previous work has examined the slope of the outer density profile and and how it affects the broadness of the features (Mazzali et al 2017). Here we concentrated on having a constant E kin /M ej but varying the over all M ej .…”
Section: Discussionmentioning
confidence: 99%
“…By moddeling only the photospheric phase spectra we found that the errors on M ej were 20%, and because of this so were the errors on E kin . However for an individual M ej the error on E kin is much smaller (see Mazzali et al (2017)). Furthermore, simultaneous photopsheric phase, nebular phase, and bolometric light curves models would dramatically reduce the error on M ej .…”
Section: Discussionmentioning
confidence: 99%